1995
DOI: 10.1089/aid.1995.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Integrase by a Hydrophobic Cation: The Phenanthroline-Cuprous Complex

Abstract: The human immunodeficiency virus type 1 integrase (HIV-1 integrase) is required for integration of a double-stranded DNA copy of the viral RNA genome into a host chromosome and for HIV replication. We have examined the effects of 2:1 1,10-phenanthroline-cuprous complexes on purified HIV-1 integrase. Although the uncomplexed phenanthrolines are not active below 100 microM, four of the cuprous complexes (neocuproine, 4-phenyl neocuproine, 2,3,4,7,8,9-hexamethyl phenanthroline, and 2,3,4,7,8-pentamethyl phenanthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…To date, most inhibitors of HIV IN belong to the class of low-molecular-mass compounds identified from natural sources and chemical libraries. Examples for these mainly aromatic compounds are: caffeic acid phenethyl ester and its derivatives [124][125][126], flavones [126,127], tyrphostins [128], bis-catechols [129], lignans [130], aurintricarboxylic acid [131], curcumin [132,133], phenanthroline-cuprous complex [134], dicaffeoylquinic acid [135] and cosalane analogues [136] (see Table 1). Structure-activityrelationship analysis demonstrated that most of these compounds contain aromatic polyhydroxylated aromatic rings separated by an aliphatic spacer [125].…”
Section: Hiv In Inhibitorsmentioning
confidence: 99%
“…To date, most inhibitors of HIV IN belong to the class of low-molecular-mass compounds identified from natural sources and chemical libraries. Examples for these mainly aromatic compounds are: caffeic acid phenethyl ester and its derivatives [124][125][126], flavones [126,127], tyrphostins [128], bis-catechols [129], lignans [130], aurintricarboxylic acid [131], curcumin [132,133], phenanthroline-cuprous complex [134], dicaffeoylquinic acid [135] and cosalane analogues [136] (see Table 1). Structure-activityrelationship analysis demonstrated that most of these compounds contain aromatic polyhydroxylated aromatic rings separated by an aliphatic spacer [125].…”
Section: Hiv In Inhibitorsmentioning
confidence: 99%
“…: enzymes involved in oxidative phosphorylation, human immunodeficiency virus type 1 integrase) functions. Such modulatory effects are brought about by its specific direct binding to the enzyme catalytic core site and not through its chelation property.…”
Section: Discussionmentioning
confidence: 99%
“…Even though free 1,10-phenanthrolines are inactive at concentrations below 100 µM, Cu(I) bis-1,10-phenanthroline complexes with neocuproine, 4-phenylneocuproine, as well as 2,3,4,-7,8,9-hexamethyl-1,10-phenanthroline and 2,3,4,7,8-pentamethyl-1,10-phenanthroline inhibit HIV-I viruses (IC 50 for integrative ranging vary between 1 and 10 µM). Disintegrative inhibition by these complexes occurs at slightly higher concentrations, between 10 and 40 µM) [151,152].…”
Section: Redox-assisted Antibacterial Antiviral and Antitumor Effecmentioning
confidence: 98%
“…Over the past years the complexes of transition metals, especially Cu(I), with 1,10-phenanthroline and its derivatives (neocuproine, 4-phenylneocuproine, bathocuproine dusolfonic acid) have attracted enhanced interest as agents inhibiting HIV-1 and HIV-2 viruces [151][152][153][154]. Heterocyclic agents inhibiting HIV-1 and HIV-2 viruses at 50% inhibitory concentrations (IC 50 ) of 0.006 and 0.01 µg ml -1 , respectively, were synthesized on the basis of 2,9-bis(bromomethyl)-1,10-phenanthroline [155].…”
Section: Redox-assisted Antibacterial Antiviral and Antitumor Effecmentioning
confidence: 99%